Testing the Model of the Effect of IT Governance on Digital Transformation and Ministry of A Performance Using Structural Equation Modeling - Dinda Sekar Cendani; Rahmat Mulyana; Lukman Abdurrahman (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Along with the latest technological disruption, changes in stakeholder behavior towards digital and the Covid-19 pandemic have directed various organizations to accelerate digital transformation (DT). However, there have been many failures in DT investments, which are thought to be due to a lack of governance. Previous research has identified the effect of traditional and agile/adaptive ITG on the success of TD in the private sector. Therefore, testing the model of the influence of ITG on DT and organizational performance (OP) in the public sector was conducted. This study took a case study of DT ministry A which has received many DT awards. The survey was conducted by distributing e-questionnaires to 50 respondents, then analyzed using Structural Equation Modeling. The results showed that traditional and agile/adaptive TKTI mechanisms had a positive and significant effect on BP and TD on KO. This research contributes to the knowledge base and becomes a reference for implementing the hybrid TKTI mechanism for TD and KO in the public sector.